The THE EFFECT OF EXCHANGE RATE, INFLATION, AND INTEREST RATE ON REAL INVESTMENT IN INDONESIA 2004-2023 (VECM APPROACH) - Tanasya, Levina Faza; Susanto, Is (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Economic globalization has brought Indonesia into the flow of global economic integration, strengthening interconnectedness between countries and increasing the intensity of competition and investment flows, both domestic and international. In this context, real investment is a vital component for national economic growth, but remains influenced by dynamic fluctuations in exchange rates, inflation, and interest rates. This study aims to empirically analyze the influence of exchange rates, inflation, and interest rates on real investment in Indonesia for the period 2004–2023, highlighting their relevance from an Islamic economic perspective. This study uses a quantitative approach with 20 years of time series data obtained from Bank Indonesia and the Central Bureau of Statistics, and applies the Vector Error Correction Model (VECM) to examine the short-term and long-term relationships between variables. The results show that in the long run, the exchange rate and inflation have a negative and significant effect on real investment, while interest rates have a positive and significant effect. Conversely, in the short run, only inflation has been shown to have a significant negative effect on real investment, while the exchange rate and interest rates have no significant effect. These findings emphasize the importance of exchange rate stability and inflation control in creating a conducive investment climate, as well as the need for adaptive policies related to interest rates. From an Islamic economic perspective, exchange rate stability, inflation control, and the elimination of interest rates (riba) are crucial for encouraging fair and sustainable real investment, thus supporting inclusive economic growth in accordance with the principles of justice and balance.